PEMANTAUAN KERUSAKAN LINGKUNGAN WILAYAH MERATUS, KALIMANTAN SELATAN DARI CITRA LANDSAT-TM DENGAN KAJIAN GEOGRAFIS - Florentina Sri Hardiyanti; Kiki Taufik; Laju Gadharum; - Rambo (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2006)
There are some damages in the evironment of the forest areas of Meratus mountainous, South Kalimantan. It's damaged one side in slope areas. Land conversion whitout consideringthe conservation has contributed to the damaged. The method of the evironment monitiring studies is by using the remote sensing and the geographic information system. The amount of the evironment gradation is 398.820 Ha. Its gradation is in the forest conservation area and in the tropical forest in montainous, slope, basin and swamp forest. Bushes are covered up to 108.750 Ha. Wisdom reforms and social culture are responsible for the physical damages of the evironment.